Stern-Gerlach centennial: Parity, gradient effect, and an analogy with the Higgs field - Bulnes, J.D.; Travassos, M.A.I.; Juraev, D.A.; Ottoni, J.E.; Lopez-Bonilla, J. (Himalayan Physics, 2024)
In this article, which celebrates 100 years of the Stern-Gerlach experiment, we identify and discuss some limitations of the mathematical field we intend to represent as the Stern-Gerlach magnetic field. We extend some recent theoretical results concerning Stern-Gerlach eigenenergies, where what we call “the gradient effect” manifests itself: the contribution of the magnetic field gradient to the self-energies. Finally, based on an analogy with the Stern-Gerlach effect, we visualized that the Higgs field must be homogeneous in its minimum energy configuration within the context of the Higgs mass generation mechanism.